Julius Caesar. - Gunther, John, 1901-1970.; Cellini, Joseph (New York, Random House, 1959)
A biography of Caesar, scholar and leader, whom historians described as the first modern man.
Keywords: Caesar, Julius -- Juvenile literature; Caesar, Julius; Heads of state -- Italy -- Rome -- Biography -- Juvenile literature; Generals -- Italy -- Rome -- Biography -- Juvenile literature; Rome (Italy) -- History -- Republic, 265-30 B.C. -- Juvenile literature